Proving The Hope In Goal"The Dream Begins" Movie Directed By Danny Cannon (2005): An Individual Psychological Approach - Sadono, Ristiawan (2012)
This research paper elaborates proving the hope in Goal movie, which was analyzed through individual psychological approach. The objectives of the research are to analyze the movie based on its structural elements and to analyze the movie especially the main character based on the individual psychological approach. The researcher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the events of the movie and script of Goal and the secondary data source is collected from other literatures discussing about individual psychoanalytic, literary books, criticism, and some article related to the movie. The method of collecting data is documentation. The technique of analyzing data is descriptive. The results of the study are as follows. First based on the structural analysis, the element of the story such as character and characterization, plot, setting, point of view, theme, style are structurally in unity and related one another in building the story. Second based on Individual Psychological approach, Proving the hope reflected in his fiction finalism, inferiority feeling, striving for superiority, style of live, social interest, and creative power.